Organized labor in Latin America : historical case studies or workers in dependence societies. - Spalding, Hobart A. (New York University Press, 1977)
Analiza la organización de los movimientos obreros en América Latina entre 1850 y 1960. Examina los casos de México, Argentina, Brasil, Bolivia y Cuba.